Entrepreneurial Assistance for Marketing Virgin Coconut Oil (VCO) Products for Multicultural Class Students at Bakti Karya Parigi Vocational - Hikmah Maulani; Nur Muthmainah; Tatang Tatang; Nalahuddin Saleh; Shofa Musthofa Khalid (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity program aims to accommodate student creativity in efforts to develop entrepreneurship in the digital era by utilizing community environmental commodities and technology. The methods for implementing community service activities were processing assistance virgin coconut oil (VCO), packaging and marketing in social media. The target of the activity was the selling value of this VCO innovation is expected to generate economic value that is beneficial not only for students and schools but also for the community. Bakti Karya Vocational School is a multimedia vocational school; with this provision, students can learn to manage marketing through multimedia. The instrument for this activity used observation to see things naturally and observe the process from gathering materials to selling. Besides that, other instruments used were in-depth interviews with entrepreneurship supervisors (teachers), the surrounding community as material suppliers, and students as actors of entrepreneurial activities and then analyzed descriptively. The results of this service activity conclude that this activity generates program ideas about effective sales patterns through social media, introducing Virgin Coconut Oil (VCO) products through Multicultural class volunteers. Through observation, the media was effective as a marketing medium, but packaging determines the attractiveness of potential buyers. Through this assistance, students gained a new enthusiasm with the confidence that the products they produce had a sale value. This assistance collected materials through the community around the school, which fosters the value of social communication for students and the community, as well as good communication between the school and the community. The results obtained are not just product selling points and marketing, but another value is the growth of students' self-reliance and social values that are intertwined between students, schools, and the community environment.